Real earnings management in companies punished by the UKNF for irregularities regarding IAS/IFRS principles - Comporek, Michał (Realne zarządzanie zyskiem w spółkach ukaranych przez KNF za nieprzestrzeganie wytycznych MSR/MSSF, 2020)
The main purpose of the paper is to assess the scope the real earnings management (REM) practices in 20 industrial public companies punished by the Polish Financial Supervision Authority (UKNF) for irregularities regarding compliance with IAS/IFSR. Such a group of violations includes a wide spectrum of irregularities related to: measuring impairment of assets, deviations from accounting standards regarding financial instruments, inadequate fair value measurement, lack of appropriate disclosures, delaying inside information, etc. The empirical research focuses on finding an answer to the question whether the level of REM practices (computed by the Roychowdhury models) in the preceding or following periods differs in a statistically significant manner from the REM activities calculated for the period in which the irregularities were detected. On the other hand, the second approach seeks to examine the relationships between REM and accrual-based earnings management (AEM) practices used to intentionally create financial results in industrial public companies in the tested sample. The conducted research, due to its uniqueness from the perspective of the Polish capital market, seems to be important from the point of view of searching for precise tools to assess the quality of financial statements of public companies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 17-30